EVALUASI MUTU SABUN PADAT DENGAN PENAMBAHAN VARIASI EKSTRAK ETANOL TEMBAKAU (Nicotiana tabacum L.) - Dini Kusuma Ningrum; Andi Eko Wiyono; Winda Amilia (EnviroScienteae, 2021)
The extract of tobacco leaves can also be used as a natural addition in making a hard soap. Hard soap from tobacco extracts produced must comply with the quality requirements specified by Indonesian National Standard (abbreviated SNI-3532: 2016). The objective of this study is to evaluate the quality of solid soap preparations with the addition of variations in the ethanol extract of tobacco. The method used is a laboratory experimental method using descriptive analysis. The concentration of tobacco extract used was 0 g, 1.2 g, 2.4 g, and 4.8 g. A testing parameter is used including water content, total fat, ethanol-insoluble, alkaline free, chloride content, and non-soapy fat as well. The result of study indicates that a hard soap containing of water content range between 13,45% to 14,37, total fat range between 65,88% to 66,63%, ethanol-insoluble range between 3,97% to 4,31%, alkaline free range between 0,056% to 0,0584%, chloride content range between 0,61% to 0,87% and non-soapy fat range between 0,3% to 0,36%. The results of the study for solid soap obtained is in accordance with Indonesian National Standards so that this kind of soap is safe for use by the public.